Critical Management Studies, cooperatives and emancipation in Mexico and Europe - Ayvar Acosta, Maria Ivette (Cooperativismo & Desarrollo, 2022)
According to the International Cooperative Alliance, there are more than 3 million cooperatives, generating income of more than 2,000 billion dollars a year. This article aims to identify, from the Critical Management Studies, strategies developed in cooperatives that express an emancipatory potential and transform management theories with their practice. This is a qualitative study, on a sample of six cooperatives in Mexico and Europe, through in-depth interviews conducted with the managers of the cooperatives. The main results of the research are that self-management, consensus, trust and participation represent emancipatory practices and that, the less cooperatives are present in the capitalist market, the greater their emancipatory potential.
Keywords: cooperativism; emancipatory potential; critical theory; Administration